DI-052 Developing an interactive tool to educate patients on good management of drugs. (25th February 2017) - Gschwind, L; Folch, C; Bonnabry, P
Abstract : Background: Involving the patient in his drug therapy is essential and contributes to improving his empowerment. Currently, there are few reliable educational tools addressing general information on the good management of drugs by patients. Purpose: To develop and evaluate an interactive educational tool focusing on general information on drugs specifically for patients. Material and methods: Organisation of focus groups with patients and healthcare professionals to identify patient's needs regarding general information on drugs. Organisation of two sessions of 2 hours for each category of participants. Creation of the interactive educational tool into an e-Learning format (Software Articulate Storyline 1). Evaluation of the impact of the e-Learning on participants' knowledge (globally and divided into three age categories: 18–30; 31–65; >65 years) by comparing the number of good answers and the degree of certitude (scale 1 to 5) for each answer to multiple choice questions before and after e-Learning completion. Satisfaction evaluation through a standardised questionnaire. Results: Identification and selection of four topics to integrate into the e-Learning: patient treatment card, travelling with medication, conservation and storage of drugs, and sources of information. 77 participants were enrolled. After e-Learning, the global percentage of good answers improved significantly: 53.7% before (pre-test) and 74.4% after e-Learning (post-test) (p<0.001). The degree of certitude improved significantly: 3.84 at the pre-test and 4.75 at the post-test (p<0.001). All participants (99.9%) were satisfied or very satisfied with this educational tool. 89.6% found the difficulty level of the course in accordance with their knowledge. The category of age had no significant impact on the improvement of knowledge or on satisfaction. Conclusion: This study allowed us to develop and evaluate a reliable interactive tool on general drug information for patients. The e-Learning improved significantly the knowledge and degree of certitude of participants. The vast majority were satisfied with this tool. In the future, it would be interesting to develop additional topics and to allow healthcare professionals to use this e-Learning to educate their patients. No conflict of interest